Acute spinal epidural abscess. Observations from fourteen cases. Issue 648 (October 1979) - Phillips, G. E.; Jefferson, A.
Abstract : Fourteen cases of acute spinal epidural abscess are analysed. Postoperatively 6 recovered completely, 4 patients recovered enough to allow unaided walking, 2 died and 2 who were paraplegic pre-operatively remained so. The purpose of this paper is to remind readers of the existence of this condition and to plead for early diagnosis and prompt surgical treatment.